Effects of bee bread on cardiovascular parameters in high-fat diet-induced obese rats - Zaidatul Akmal Othman; Universiti Sains Malaysia . School of Medical Science (2018)
Obesity is characterised by excessive fat accumulation in the body thereby contributing to cardiovascular disease particularly hyperlipidaemia, hypertension and atherosclerosis. Bee bread is a natural product used traditionally to maintain and improve general health. However, its possible protective effect on cardiovascular parameters in high-fat diet (HFD) induced obese rats has not yet established. The objectives of this study were (I) to evaluate and analyse nutritional, phytochemical and antioxidant activity of bee bread of stingless bee (Heterotrigona itama) from three different regions in Malaysia namely Kelantan, Selangor and Perak (Phase 1 Study), (2) to establish animal model of obesity and to determine the best dose of bee bread (Phase 2 Study), and (3) to determine the effects of bee bread on cardiovascular parameters in HFD induced obese rats (Phase 3 Study). In Phase 2 study, different doses of bee bread (0.5, 1.0 and 1.5 g/kg/day) were administered to HFD-induced obese rats via oral gavage for 6 week. In Phase 3 study, cardioprotective and antioxidative effects of bee bread (0.5 g/kg/day) and orlistat (10 rng/kg/day) were determined in HFD-induced obese rats. At the end of the experiment, rats were sacrificed to assess cardiovascular parameters such as Lee obesity index, food and calorie intake, lipid profiles, adiposity and atherogenic index, antioxidative status, and histology of aortic arch, adipose tissue and myocardium. All bee bread samples had relatively high nutritional value, amino acids, phytochemical and in-vitro antioxidant activities. Highest total phenolic and flavonoid contents were found in bee bread sample from Perak whereby highest free radical scavenging activity was found in sample from Selangor. Bee bread at the dose of 0.5 g/kg/day was chosen as the best dose as it reduced the Lee obesity index, total cholesterol, and low-density lipoprotein (LDL) in HFD-induced obese rats. Bee bread exerts protective effects against the risk of cardiovascular disease as it significantly reduced Lee obesity index and levels of total cholesterol, LDL, oxidised-LDL and malondialdehyde, as well as significantly increased the antioxidant activities such as superoxide dismutase and glutathione peroxidase in aortic tissues. Bee bread also significantly reduced fatty acid synthase activity, size of adipocytes and area of necrotic patch in myocardium compared to HFD group. There was an absence of atherosclerotic plaque in aortic arch segment in rats supplemented with bee bread. This study suggests that bee bread supplementation at 0.5 g/kg/day for 6 weeks significantly protects against obesity, hyperlipidaemia, oxidative stress and atherosclerotic plaque formation possibly by increasing antioxidant enzymes activities and decreasing fatty acid synthase activity in HFD-induced obese rats. These beneficial effects could be attributed to the presence of phytochemical compounds such as apigenin, caffeic acids, ferulic acids, isorhamnetin and kaempferol in bee bread. These findings may indicate the potential use of bee bread in reducing the risk of cardiovascular disease which needs further study to determineits exact molecular mechanism of action.
1. Introduction -- 2. Literature review -- 3. Materials and methods -- 4. Results -- 5. Discussion -- 6. Summary -- 7. Limitation of study and recommendation for future research
Thesis (Degree of Master of Science) - Universiti Sains Malaysia, 2018
Includes bibliographical references (p. 137-154)
Keywords: Universiti Sains Malaysia -- School of Medical Science -- Dissertations; Biochemistry; Diet, High-Fat; Obesity -- Nutritional aspects; Propolis